A novel ROS-responsive nanocarrier for antioxidant therapy in endodontic inflammation - WANG Mingxin, DUAN Yiyuan, FENG Kejia, NIE Chenyu, MA Qian (Kouqiang yixue)
Objective To explore the effects of cerium-doped mesoporous bioactive glass nanoparticles (Ce-MBGNs) as reactive oxygen species (ROS)-responsive nanocarriers on inflammation in pulp and their potential to promote odontogenic differentiation of dental pulp stem cells (DPSCs). Methods The cytotoxicity of Ce-MBGNs was assessed by CCK-8. The expression of mRNA of osteogenic/odontogenic differentiation in DPSCs and that of inflammatory factor in RAW264.7 cells were detected by RT-qPCR. Alkaline phosphatase and Alizarin Red S staining were utilized to investigate their ability to promote dentin mineralization. The ability of Ce-MBGNs to scavenge ROS was evaluated by immunofluorescence and JC-1 staining was used to assess the membrane potential (MMP) of mitochondrial. Results Ce-MBGNs exhibited good biocompatibility and significantly increased the expression of osteogenic/odontogenic-related genes in DPSCs, promoting mineralization. Additionally, Ce-MBGNs effectively scavenged intracellular ROS, maintained MMP, inhibited the expression of pro-inflammatory factors, and promoted the expression of anti-inflammatory factors. Conclusion Ce-MBGNs can protect DPSCs from oxidative damage by maintaining the MMP of mitochondrial and controlling inflammation, and promote their odontoblastic differentiation, providing a theoretical basis for the development of novel therapeutic agents for oral treatment.